2001
DOI: 10.1111/0022-4537.00203
|View full text |Cite
|
Sign up to set email alerts
|

Coping With Ethnic Stereotypes in the Academic Domain: Perceived Injustice and Psychological Disengagement

Abstract: Psychological disengagement is the defensive detachment of self-esteem from a particular domain. In the academic arena, disengagement can result from devaluing academic success or discounting the validity of academic outcomes. We review evidence for ethnic differences in these two processes of psychological disengagement and present results of a multiethnic study examining perceived ethnic injustice and academic performance as predictors of devaluing and discounting. Among African American students, beliefs ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
250
1
9

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(276 citation statements)
references
References 46 publications
16
250
1
9
Order By: Relevance
“…This is important because studies have found that stereotype threat effects can lead to VERTICAL COLLECTIVISM AND STEREOTYPE THREAT 21 disengagement with the academic domain (Schmader, Major, & Gramzow, 2001), which might amplify educational disadvantages (e.g., Kristen et al, 2008). Second, the deployment of these temporary individual mobility strategies should be valued by their own group because it is consistent with the group's achievement expectations (Phalet & Claeys, 1993), and thus should reduce potential worries about not living up to the group's expectations.…”
Section: Effects Of Coping Strategiesmentioning
confidence: 99%
“…This is important because studies have found that stereotype threat effects can lead to VERTICAL COLLECTIVISM AND STEREOTYPE THREAT 21 disengagement with the academic domain (Schmader, Major, & Gramzow, 2001), which might amplify educational disadvantages (e.g., Kristen et al, 2008). Second, the deployment of these temporary individual mobility strategies should be valued by their own group because it is consistent with the group's achievement expectations (Phalet & Claeys, 1993), and thus should reduce potential worries about not living up to the group's expectations.…”
Section: Effects Of Coping Strategiesmentioning
confidence: 99%
“…This scale measures the extent to which students enjoy and are interested in the course. We measured individual interest with a 4-item "Devaluing" scale (Schmader, Major, & Gramzow, 2001) that was reverse coded by Jones (2010a) to measure the extent to which students found the courses to be important and valuable. We measured academic caring using the 4-item Teacher Academic Support scale and personal caring using the 4-item Teacher Personal Support scale, both of which are subscales of the Classroom Life Instrument (Johnson et al, 1983).…”
Section: Quantitative Phasementioning
confidence: 99%
“…When discrimination is detected, perceptions of personal control may be reduced such that members of low-status groups may be less likely to identify actions that could ameliorate the patronizing and anger-inspiring situation. As a result, group-based inequities may be associated with performance decrements among low-status but not highstatus group members (Schmader, Major, & Gramzow, 2001). …”
Section: What Effects Do Patronizing Behaviors Have On Low-power People?mentioning
confidence: 99%